FACTORS AND APPROACHES TO RESTORING PHYSICAL ACTIVITY IN SCHOOLCHILDREN IN THE POST-COVID-19 PERIOD: A SYSTEMATIC REVIEW - Galan, Y. P.; Moldovan, A. D.; Brazhaniuk, A. O. (My University, 2026)
During the COVID-19 pandemic and in the post-pandemic period, the decline in physical activity (PA) among school-age children became more pronounced. It highlighted the need for systematic measures to support physical activity at the school and community levels. This exacerbated the risks to physical and mental health and increased the need for rapid, evidence-based solutions at the education level. At the same time, international and European policy frameworks explicitly emphasize the need to systematically promote Health-Enhancing Physical Activity (HEPA) as a resource for recovery, resilience, and long-term prevention, particularly in the educational environment. The purpose of the study is to systematically analyse and summarize international experience on effective factors and approaches to increasing physical activity among schoolchildren aged 6–18 during the COVID-19 pandemic and in the post-COVID-19 period, identifying the most promising for adaptation and integration in the current conditions of Ukraine. Research methods. A systematic review was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol by searching the Scopus database (TITLE-ABS-KEY) for open-access English-language articles for 2021–2024 on approaches to increasing the physical activity of schoolchildren aged 6–18 during the COVID-19 pandemic and in the post-pandemic period. Results. The studies included in the analysis showed that in the post-pandemic (post-COVID-19) period, the recovery of physical activity among schoolchildren is uneven and does not occur automatically. Higher levels of physical activity and more favourable well-being indicators are more often associated with organized school-based forms of physical activity, an emphasis on vigorous physical activities (VPA), social and psychological support, stabilization of daily routines (sleep, reduction of screen time), and outdoor activities. In contrast, digital interventions of an informational nature without components of active involvement and support tend to have a limited effect. Conclusions. To sustainably restore physical activity levels among schoolchildren aged 6–18 during the COVID-19 pandemic and after the easing or lifting of restrictive measures, it is advisable to implement multi-component programs in the school environment. In the post-pandemic (post-COVID-19) period, the recovery of physical activity among schoolchildren is uneven. It is most consistently supported by organized activities in the school environment, social and psychological support, normalization of sleep, and reduction of screen time.
Keywords: physical activity; school-based intervention; physical education; adolescents; schoolchildren; return to school; COVID-19; strategies; programs; digital models